2014
DOI: 10.1002/ase.1463
|View full text |Cite
|
Sign up to set email alerts
|

Assessing student engagement and self‐regulated learning in a medical gross anatomy course

Abstract: In courses with large enrollment, faculty members sometimes struggle with an understanding of how individual students are engaging in their courses. Information about the level of student engagement that instructors would likely find most useful can be linked to: (1) the learning strategies that students are using; (2) the barriers to learning that students are encountering; and (3) whether the course materials and activities are yielding the intended learning outcomes. This study drew upon self-regulated lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
6
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 23 publications
4
66
6
4
Order By: Relevance
“…Finally, the individual differences within students, such as spatial abilities and the daily fluctuations in motivation and cognitive load, will determine the impact such a resource has on learning. Many of these confounding variables are well documented in the literature and should be used in conjunction with the evaluation's findings on learner impact when drawing conclusions (Krause and Coates, ; Burgoon et al, ; Pizzimenti and Axelson, ; Abdel Meguid and Khalil, ; Iqbal, ; Pickering, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the individual differences within students, such as spatial abilities and the daily fluctuations in motivation and cognitive load, will determine the impact such a resource has on learning. Many of these confounding variables are well documented in the literature and should be used in conjunction with the evaluation's findings on learner impact when drawing conclusions (Krause and Coates, ; Burgoon et al, ; Pizzimenti and Axelson, ; Abdel Meguid and Khalil, ; Iqbal, ; Pickering, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that preference for a particular mode of instruction is not correlated with improved productivity among those who experience their preferred instructional technique [23]. Others have suggested that self-regulated learning theory should be invoked to explain the relationship between students’ learning engagement and academic performance in anatomy courses [24]. Self-regulated learning theory focuses on the active participation of students in personal, behavioural, motivational, and cognitive efforts to achieve valued academic goals.…”
Section: Discussionmentioning
confidence: 99%
“…Self-regulated learning theory focuses on the active participation of students in personal, behavioural, motivational, and cognitive efforts to achieve valued academic goals. In this context, level of self-regulation modulates students’ employment of learning strategies, engagement with anatomy course material, and the extent to which activities and taught sessions are linked with expected learning outcomes [24]. Therefore, a failure of self-regulation might underlie the reported disconnect between preferred teaching methods and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument has been used in a wide range of population groups, from students in primary schools to those in higher education. Several studies have used the MSLQ as part of medical education research and have found associations between MSLQ scores and academic achievement [6, 3739]. One preliminary study used the MSLQ to measure the changes in SRL of preclinical medical students that occurred between the first and second year of their course [40].…”
Section: Methodsmentioning
confidence: 99%